Diskriminasi Sosial Pada Tokoh Utama Dalam Film Rio The Survivor Disutradai Oleh Yudie Oktav - Dinna Juniary; Alifiah Nurachmana; Linggua Sanjaya Usop; Hartini Hartini; Bainah Bainah; Dila Dila (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
This research discusses social discrimination among characters in the film Rio The Survivor directed by Yudie Oktav. Therefore, the aim of this research is to: (1) describe the representation of dialogue containing social discrimination in the film Rio The Survivor directed by Yudie Oktav, (2) describe the representation of the causes of social discrimination in the film Rio The Survivor directed by Yudie Oktav, (3 ) describes the implications of social discrimination on drama learning in high school. This research uses a qualitative research method with a descriptive approach and data is taken from the film Rio The Survivor directed by Yudie Oktav in the form of screenshots of film footage and dialogue between characters which contain social discrimination. The results of research on social discrimination on the main character in the film Rio The Survivor directed by Yudie Oktav show that (1) social discrimination which includes direct discrimination: limiting a certain area, such as housing, type of work, public facilities, and indirect: the act of blocking someone/ certain groups, races/ethnicities relate freely, hinder the rules/procedures followed which contain discriminatory bias and result in harm to the main character, a child living with HIV/AIDS, (2) the cause of social discrimination in the film Rio The Survivor directed by Yudie Oktav is caused by due to the lack of public knowledge about HIV/AIDS, (3) The results of this research have implications for Drama Learning in Class XI SMA, especially in competency identifying characterization, dialogue and setting in drama performances.